Alkyl length dependent mechanofluorochromism of AIE-based phenothiazinyl fluorophenyl acrylonitrile derivatives. (January 2017) - Ma, Chunping; Zhang, Xiqi; Yang, Liutao; Li, Yang; Liu, Hongliang; Yang, Yang; Xie, Gaoyi; Ou, Yong-Cong; Wei, Yen
Abstract: Four alkyl phenothiazinyl fluorophenyl acrylonitrile derivatives (PhC3F, PhC6F, PhC10F, andPhC12F ) with different length of alkyl chains were synthesized in high yield. The compounds showed obvious aggregation-induced emission (AIE) and alkyl length dependent mechanofluorochromic (MFC) properties.PhC3F with propyl chain andPhC12F with dodecyl chain showed obvious and reversible MFC behaviours, whilePhC6F with hexyl chain andPhC10F with decyl chain exhibited little MFC property. Small and wide-angle X-ray scattering indicated the MFC behaviour ofPhC3F andPhC12F were attributed to the phase transformation from crystalline to amorphous state, whilePhC6F maintained excellent crystalline performance before and after grinding, which was also evidenced by differential scanning calorimetry result. Quantum mechanical computations further revealedPhC6F had high molecular polarity, which greatly improved its crystalline performance, and made its original aggregated morphology hard to damage, then brought about little MFC diversification.PhC10F showed the highest molecular polarity and least MFC behaviour. We concluded that obvious MFC feature derived from appropriate crystalline performance, favourable molecular polarity and energy gap. Highlights: Four acrylonitrile derivatives with different length of alkyl chains were synthesized. The derivatives exhibited aggregation-induced emission feature. The derivatives showed alkyl length dependent mechanofluorochromism. The mechanofluorochromism was affected by molecular polarity and crystalline performance.